TALENT ATTRACTION, TALENT RETENTION, AND TALENT MANAGEMENT AS A MEDIATING ON ORGANIZATION PERFORMANCE - Sembiring, Edward; Damayanti, Nur (ULTIMA Management, 2023)
Abstract- An effective human resource management system is related to people, policies, and systems that affect the workforce. An organization consists of labor, money, materials, and machines. When an organization prepares to compete globally, it must have skilled workers that strengthen their intelligence to develop the market and apply the best organizational learning practices. Human resource quantity and quality are directly proportional to organizational performance and productivity. One of the most difficult challenges in management is developing and retaining a workforce that contributes to organizational performance. This study investigates the impact of human resource management on talent attraction, talent management, and talent management on organizational performance in large-scale and coal maining companies. This study uses SPSS 2.6 version to analyze 119 respondents. Results of this study are talent attraction significantly impacts talent management, talent retention significantly influence talent management. Talent attraction significantly affects organizational performance, talent retention did not influence employee performance. Talent management has a significant influence on employee performance. Talent attraction has a significant impact on organizational performance mediated by talent management and talent management variable as a mediating variable helps talent retention by providing an indirect effect on organizational performance.. The limitations of this study are cross-sectional empirical studies and the variables in this study are measured based on the responses of top and middle management staff only. The research findings suggest that further research should examine other fields related to human resources, especially focusing on the influence of talent retention on organizational performance and talent attraction on organizational performance through talent management as a mediating variable with different dimensions and elements. Keywords: Mining Industry; Talent Attraction; Talent Retention; Talent Management; Organizational Performance